Wensters new collegiate dictionary, / a Merriam -Webster - Webster, Merriam (Estados Unidos de América: G & C. Merriam company springfield, mass, 1973)
Explanatory chart, notes, the english language and its history, abbreviations in this work, pronunciation symbols; dictionary of english languge, foreign words and phrases, biographical names, colleges and universities, signs and symbols, a handbook of style.
Contenido, ilustración
Col. Ref
Keywords: 1. DICCIONARIO 2. COLLEGIATE DICTIONARY 3. REFERENCIA